The Voting Behavior of Kyai And Santri on the Legislative Election of 2019 - Siswanto, Akhorin; Supriyadi, Supriyadi; Zuber, Ahmad (International Journal Labs, 2022)
Background: Kyai and Santri have a long history in the political dynamics of the Indonesian nation. In addition, the number of Islamic boarding schools and students has experienced significant development, so it is not surprising that Islamic boarding schools are land to gain votes in the general election of legislative candidates. Aim: This study aims to describe the behavior of Kyai voters in the 2019 Legislative Election and the behavior of Santri voters in the 2019 Legislative Election. Method: The research uses descriptive qualitative with a case study at the Wisma Wisnu Islamic Boarding School, Madiun Regency. Data analysis was carried out using the approach of sociological theory (The Colombia Study) and rational choice. Findings: The results showed that; 1) The behavior of Kyai voters in the 2019 Legislative Elections showed a rational choice approach. Kyai was able to assess the quality, competence, and integrity of legislative candidates through vision, mission, and programs; 2) The behavior of Santri voters in the 2019 Legislative General Election showed a sociological approach (The Colombia Study); Santri did not know the vision and program of the future legislative because the students were not involved in the campaign stage, so the consideration in determining the choice of students was due to the direction of the Kyai and partly because of the supervision of the parents.